Novel highly specific anti‐periostin antibodies uncover the functional importance of the fascilin 1‐1 domain and highlight preferential expression of periostin in aggressive breast cancer. Issue 8 (21st December 2015) - Field, Sarah; Uyttenhove, Catherine; Stroobant, Vincent; Cheou, Paméla; Donckers, Dominique; Coutelier, Jean‐Paul; Simpson, Peter T.; Cummings, Margaret C.; Saunus, Jodi M.; Reid, Lynne E.; Kutasovic, Jamie R.; McNicol, Anne Marie; et al.
Abstract : Periostin (POSTN), a secreted homodimeric protein that binds integrins αvβ3, αvβ5, and α6β4, was originally found to be expressed in fetal tissues and in the adult upon injury particularly bone fractures due to its role in remodelling and repair. Recently it was found to be over‐expressed in human breast cancer and a variety of other tumour types including head and neck squamous cell carcinoma, where its overexpression correlates with increased tumour invasion. Progress in studying its functional role in tumour pathogenesis has been hampered by the paucity of antibodies for its specific and sensitive detection. It has proven very difficult to obtain monoclonal antibodies (mAbs) against this highly conserved protein but we report here that combining infection of mice with lactate dehydrogenase elevating virus (LDV), a B cell activating arterivirus, with conjugation of human POSTN to ovalbumin as an immunogenic carrier, enabled us to develop six mAbs recognizing both human and mouse POSTN and inhibiting its binding to αvβ3 integrin. Two of the mAbs, MPB4B1 and MPC5B4, were tested and found to inhibit POSTN‐induced migration of human endothelial colony forming cells. All six mAbs recognized amino acids 136‐51 (APSNEAWDNLDSDIRR) within the POSTN fascilin (FAS) 1‐1 domain revealing the functional importance of this motif; this was further highlighted by the ability of aa 136–151 peptide to inhibit integrin‐mediated cell migration. Immunohistochemistry using MPC5B4, indicated that breast tumour cell POSTN expression was a strong prognostic indicator, along with tumour size, lymph node, and human epidermal growth factor receptor 2 (HER2) status. Abstract : What's new? Periostin, a secreted glycoprotein involved in bone injury repair, has recently gained interest in the cancer field as it is overexpressed in several tumor types and binds to various integrins. Here, the authors developed neutralizing monoclonal antibodies against human periostin using a sophisticated immunization scheme. Their results point to periostin as a strong prognostic indicator in breast cancer tissue and a potential new therapeutic target in the prevention of cancer cell migration and adhesion.